ANALYSIS OF ORGANIZATIONAL COMMUNICATIONS IN THE EARLY-AGE MARRIAGE PREVENTION PROGRAM IN THE POPULATION AND FAMILY PLANNING CONTROL OFFICE OF SUMEDANG REGENCY - Kusdinar, Rika; Gustiani, Siti Aisyah (UNIVERSITAS PAKUAN, 2020)
The purpose of the research that researchers do is to find out the extent of Organizational Communication in the Population and Family Planning Control Office of Sumedang Regency. The method used in this study is a qualitative research method which is used in research based on the philosophy of postpositivism, used to examine the natural conditions of objects, where researchers act as key instruments, data collection techniques are carried out by triangulation (combined), data analysis is inductive, and qualitative research results emphasize more meaning than generalization. The technique used in taking samples is to use purposive sampling, which is sampling based on needs, so the samples in this study were 4 people. As for what is determined to be the informant in this study are the executors who are considered to have authority, information, and are involved in organizational communication in the early marriage prevention program at the Population and Family Planning Control Office of Sumedang Regency. Based on the results of the study, researchers can describe that organizational communication in early marriage prevention programs in the Population Control and Family Planning Office of Sumedang Regency can be said to be quite good, but on the other hand there are problems regarding the flow of communication downward namely not creating integration between fields, where employees have not can innovate the process of socialization activities to the community. And in cross-channel communication that is still less effective the delivery of information by employees to the public in responding to socialization activities.